STUDY OF THE EFFECTIVENESS OF COMPOST FROM OIL PALM EMPTY FRUIT BUNCH (OPF) WASTE AS AN ALTERNATIVE SOURCE OF POTASSIUM (K) ON NUTRIENT ABSORPTION AND OIL PALM YIELD IN PANGKATAN PLANTATION OF PT. EVANS GROUP - Nadia Putri Ad'ha; Khairul Rizal; Yusmaidar Sepriani; Fitra Syawal Harahap (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Oil palm (Elaeis guineensis Jacq.) is one of Indonesia's leading plantation commodities and plays a strategic role in the national economy. The purpose of this study was to determine the effectiveness of EFB compost as an alternative source of potassium, analyze its effect on potassium nutrient uptake, and assess its impact on oil palm yields at PT Evans Group. This research method used a field experiment approach by comparing two treatments: a control treatment without EFB compost and a treatment with EFB compost at a dose of 50 kg per plant. The results showed that compost application had a positive effect on plants, as indicated by increased leaf potassium content in the compost treatment compared to the treatment without compost. Although the difference was not significant, these results indicate that compost plays a role in increasing potassium availability and uptake by plants, thus supporting better plant growth.